Performance Air conditioner on retrofitted refrigerant hydrocarbon - Pujianto, Muhammad Edi; Nugroho, Agung (Jurnal Polimesin, 2024)
Synthetic refrigerants used in air conditioner (AC) are very important in depleting the ozone layer and prohibiting global warming. This has led to the application of R32 and Musicool 22 (MC22) as a substitute for R22 because refrigerant is considered more environmentally friendly. Therefore, this research aimed to compare the performance of applying both R32 and MC22 refrigerants in 1 PK split AC using the coefficient of performance (COP) as the indicator for AC performance and compressor power consumption. MC22 filling mass was varied at 90% (202.14 grams), 100% (224.6 grams), and 110% (247.6 grams) of R32 mass, and condenser inlet temperatures at 28°C, 30°C, 32°C, and 34°C. The results showed that MC22 could be used as a viable alternative to R32 due to the higher refrigeration effect value of 332.36 kJ/kg recorded for refrigerant